Learning Processes and Acquisition of Knowledge and Skills in Training and Supervision of Psychotherapy and Counselling: A Study Protocol for a Scoping Review - Oddli, Hanne Weie; Heinonen, Erkki; Hau, Stephan; Nielsen, Jan; Esterhazy, Rachelle; Hoff, Cecilie Hillestad; Strømme, Hanne (Frontiers in Psychology, 2021)
Background: Increased awareness of the individual therapist’s vital contribution to treatment processes and outcome, and the potential role of training and supervision in this respect, warrants a close look at the empirical and theoretical literature on teaching and learning of therapists and counsellors. Methods: A scoping review of the literature will be conducted based on an overarching research question: when authors have reported on learning processes and acquisition of knowledge and skills in psychotherapy/counselling and supervision/training literature over the past 30 years (since 1990), what evidence, concepts, theories, and models have they reported? A comprehensive search strategy is carried out to identify publications indexed in Scopus, PsycINFO, and Cochrane Central Register of Controlled Trials. Publications will be sorted according to four categories: (1) conceptual/theoretical; (2) empirical (quantitative, qualitative, mixed methods); (3) review, meta-synthesis or -analysis; (4) training program/model description. Procedures for the upcoming scoping review of conceptual/theoretical, empirical, and training program/model description publications will be outlined. Conclusion: Besides clarifying existing perspectives, practices, and evidence, and documenting the shifting trends of the field during the past three decades, this scoping review identifies knowledge gaps that point to vital future directions for research and theory development. Moreover, the comprehensive scoping lays the foundation for subsequent, more focused systematic reviews that address identified key research topics more specifically.